State Policy on Banking Capital Regulation Based on Supply Chain Management - Ramazanova, Ainur; Sabitova, Assyl; Orsayeva, Raissa; Bairkenova, Gulmira; Smailova, Smailova (International Journal of Supply Chain Management, 2020)
The introduction of supply chain managements (SCM) and standardized financial instruments to improve the financial market regulation of Kazakhstan requires the reallocation of resources in favor of Islamic banking capital due to the rapid growth of their share in international finances.  Supply chain effects mean that highly levered financial intermediaries are the most efficient. Low asset volatility enables banks to safely take on high leverage; supply chain effects compel them to do so. The purpose of the research is to study the key aspects of increasing the effectiveness of state policy on banking capital regulation taking into account the supply chain management in Kazakhstan. To conduct the study, the Islamic Finance Development Indicator (IFDI) was used. This is a composite index reflecting the development of the Islamic finance industry by assessing the effectiveness of all its components in accordance with its supply chain process.  In the context of this indicator, the study focuses on the development of Islamic banking assets in Kazakhstan for the period from 2015 to 2019. It has been found that Islamic banks have a diversified business model and a high level of asset efficiency; they are more stable compared to traditional banks. Malaysia and the United Arab Emirates are the leaders in the SCM in finance industry. A model of state regulation of Islamic banking capital in Kazakhstan related to the development of Islamic banking, the capital market, Islamic non-banking and micro-finance institutions, as well as the elimination of obstacles (ijara, mudaraba, murabaha and wakala) has been proposed.  The developed model creates a number of advantages for the state: the possibility of creating a sovereign sukuk, issuing Islamic corporate securities, developing and attracting portfolio investments and alternative financing, as well as increasing the image of Kazakhstan in the development of Islamic banking capital.  is  a  meaningful  tool  for  the  banking  firms  or  the organizational  performance  and  various departmental  heads are very much aware to SCM practices for the greater banking performance.